2022
DOI: 10.3390/antibiotics11040501
|View full text |Cite
|
Sign up to set email alerts
|

Cefazolin Might Be Adequate for Perioperative Antibiotic Prophylaxis in Intra-Abdominal Infections without Sepsis: A Quality Improvement Study

Abstract: Background: The adequate choice of perioperative antibiotic prophylaxis (PAP) could influence the risk of surgical site infections (SSIs) in general surgery. A new local PAP guideline was implemented in May 2017 and set the first-generation cefazolin (CFZ) instead the second-generation cefuroxime (CXM) as the new standard prophylactic antibiotic. The aim of this study was to compare the risk of SSIs after this implementation in intra-abdominal infections (IAIs) without sepsis. Methods: We performed a single ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Therefore, continuous evaluation and surveillance of local epidemiological microbial data are mandatory to enable adaptation of empiric antibiotic therapy. It has been recently shown that the implementation of antimicrobial stewardship programs is a highly effective tool to provide these data mentioned above and to supervise antibiotic treatment in intra-abdominal infections [ 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, continuous evaluation and surveillance of local epidemiological microbial data are mandatory to enable adaptation of empiric antibiotic therapy. It has been recently shown that the implementation of antimicrobial stewardship programs is a highly effective tool to provide these data mentioned above and to supervise antibiotic treatment in intra-abdominal infections [ 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beta-lactam/beta-lactamase inhibitor combinations like Ampicillin/Sulbactam would be ideally fitting if the well-described resistance on Enterobacterales would not be an obstacle. Therefore, to avoid antibiotic resistance and to optimize patient care, antimicrobial stewardship programs represent a powerful tool for continuous evaluation and surveillance [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Predicting the pathogens and potential resistance begins by establishing if the infection is community-acquired or healthcare-associated helps discriminating the proper treatment. In case of community-acquired IAI, narrower-spectrum antibiotics are preferable [ 25 ]. Instead, for patients with healthcare-associated IAI antibiotics regimens with broader activity spectrum should be preferred.…”
Section: Sepsis Team: the Role In Intra-abdominal Infection And Emerg...mentioning
confidence: 99%
“…results in increased mortality, but there are no consistent opinions on whether timely anti-enterococcal therapy improves outcomes [ 28 , 29 , 30 ]. Moreover the variable basic physical conditions of patients with IAI and infection sources usually result in diverse incidences of enterococcal infection [ 25 ]. The use of additional agents to provide antienterococcal coverage in the management of community-acquired IAI in lower risk patients has been reported as unnecessary.…”
Section: Sepsis Team: the Role In Intra-abdominal Infection And Emerg...mentioning
confidence: 99%